Microcystin production and the dominance of toxigenic strains of cyanobacteria in lake and culture studies - LeBlanc Renaud, Susan (University of Ottawa (Canada), 2009)
Cyanobacteria produce toxic compounds with the hepatotoxic microcystins being the most commonly encountered in freshwater. Microcystins are produced by several cyanobacterial genera and show large spatial and temporal variation in aquatic ecosystems as both toxigenic and non-toxigenic strains may co-exist and reach bloom levels. The regulation of microcystin production, the ecological or physiological role(s) of microcystins, and the factors that specifically promote toxic cyanobacterial blooms are not yet well understood. The first part of this thesis tested the role of light intensity in regulating the production and composition of microcystin congeners using laboratory culture experiments. The second part, using field observations and a lake enclosure experiment, examined the effects of physical, chemical and biological variables on microcystin concentrations and the growth of toxigenic cyanobacteria in a shallow, mesotrophic lake. Throughout, chemical and molecular based methods were utilized along with traditional culture and limnological methods in order to measure microcystin production and the presence of toxigenic cyanobacteria. Light intensity had a significant effect on microcystin concentrations and congener composition. However, there were no clear advantages of either toxigenic or non-toxigenic strains in terms of their ability to grow, compete for light resources, or dominate in a mixed-culture setting. The response of each strain of Microcystis aeruginosa was unique such that generalizations could not be made between toxigenic and non-toxigenic strains in terms of their competitive ability in nature; microcystin production did not appear to impair the competitive ability of toxigenic strains. In field studies of a shallow mesotrophic lake over two years, the number of microcystin gene copy numbers (mcyD) did not correlate well with microcystin concentrations. Both within the lake and across a nutrient gradient established in in situ enclosures, the best predictor of the presence of toxigenic strains was the actual biomass of potentially toxigenic genera (mainly Anabaena and Microcystis ), rather than any particular chemical or physical variable such as light. However, both environmental and biological variables were significant in predicting actual microcystin concentrations. The combination of molecular, chemical, and taxonomic data appears necessary to understand and predict toxic cyanobacterial blooms.
Keywords: Biology, Microbiology.; Environmental Health.